The archaeology of craft and industry - Fennell, Christopher (American experience in archaeological perspective., 2021)
"In this expansive yet concise survey, Christopher Fennell discusses archaeological research from sites across the United States that once manufactured, harvested, or processed commodities, uncovering key insights into American history"--